2017
DOI: 10.1021/acs.jafc.7b04173
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Alfalfa and Calcium Salts of Long-Chain Fatty Acids Alter Protein Utilization, Microbial Populations, and Plasma Fatty Acid Profile in Holstein Freemartin Heifers

Abstract: This study presented the effects of alfalfa and calcium salts of long-chain fatty acids (CSFA) on feed intake, apparent digestibility, rumen fermentation, microbial community, plasma biochemical parameters, and fatty acid profile in Holstein freemartin heifers. Eight Holstein freemartin heifers were randomly divided into a 4 × 4 Latin Square experiment with 2 × 2 factorial diets, with or without alfalfa or CSFA. Dietary supplementation of CSFA significantly increased the apparent digestibility of dry matter, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
3
9
0
Order By: Relevance
“…As a consequence, LSO-fed kids had low rumen concentrations of both C18:3n3 and n-3 PUFA, as well as an increased n-6/n-3 ratio, whereas HLS-fed kids had low rumen concentrations of both C18:2n6c and n-6 PUFA. These observations agree with those of He et al (2017) for the relationships between Ruminobacter amylophilus abundance and n-6/n-3 ratio in the rumen of heifers consuming a diet rich in C18:3n3. They are also consistent with the observation by Cremonesi et al (2018) that supplementation with linseed grain increases C18:2n6c biohydrogenation in the goat rumen.…”
Section: Discussionsupporting
confidence: 91%
“…As a consequence, LSO-fed kids had low rumen concentrations of both C18:3n3 and n-3 PUFA, as well as an increased n-6/n-3 ratio, whereas HLS-fed kids had low rumen concentrations of both C18:2n6c and n-6 PUFA. These observations agree with those of He et al (2017) for the relationships between Ruminobacter amylophilus abundance and n-6/n-3 ratio in the rumen of heifers consuming a diet rich in C18:3n3. They are also consistent with the observation by Cremonesi et al (2018) that supplementation with linseed grain increases C18:2n6c biohydrogenation in the goat rumen.…”
Section: Discussionsupporting
confidence: 91%
“…Steers in the current study were fed dry Chinese wildrye; thus, a relatively high n-6/n-3 was observed. The Δ-9 (18) index indicates the desaturation capacity of converting C18:0 to C18:1 (He et al, 2017); thus, a negative correlation was observed between Δ-9 (18) index and concentration of C18:0 in the present study.…”
Section: Fatty Acids Profilesupporting
confidence: 54%
“…The measurement of fatty acid composition was conducted on a gas chromatograph (GC-2014 Shimadzu Corporation), which was installed with a HP-88 capillary columns (100 m × 0.25 mm ID × 0.2 μm; Agilent Technologies, Wilmington, DE, USA). The operating program was similar to our previous study (He et al, 2017) with following modifications: the pressure value of nitrogen was kept at 246.6 kPa with split ratio of 30:1. Each sample was determined in duplicate, and average value was taken as the final content.…”
Section: Fatty Acid Profile Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The decreased relative abundance of Succinivibrio in FHI and CI might be due to its lower competitive ability compared with starch-degrading bacteria, such as Ruminobacter [57]. Ruminobacter also has the ability to degrade urea and protein and use amino acids as a nitrogen source in rumen [70,76]. Hence, it is reasonable to infer that Ruminobacter might be responsible for the degradation of branched-chain amino acids into BCVFA in our study.…”
Section: Discussionmentioning
confidence: 85%